Heritage assessment - Rachel E. Spector (Universidad de Alicante, 2012)
Over time, this author has discovered that people are quite responsive to these questions. The assessment tool has proven to provide a means of helping people to focus on their "growing-up" experiences and to be able to recall and relate events of childhood in a sensitive manner. By interviewing informants, one is able to stimulate and probe an individual's memory to enable them to recall and delve into health beliefs and practices. The tool has been used in several studies and also as a part of a health assessment done in clinical practice, both in the hospital and the community settings. It has appeared to be far more sensitive in preparing people to describe health beliefs and practices if used as an interview, rather then as a fill-in type of assessment.